2018
DOI: 10.4314/ejhs.v28i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Profiles of Pregnant and Non-pregnant Women Attending at the University of Gondar Hospital, Northwest Ethiopia: A Comparative Cross-sectional Study

Abstract: BackgroundPregnancy is a natural physiological statement with hormonal and metabolic changes that helps the growth and survival of the fetus. However, biochemical profiles derangement may lead to pregnancy complications. Therefore, there is a need for determining biochemical profiles among pregnant women.MethodsA comparative cross-sectional study was conducted among pregnant and non-pregnant women at the University of Gondar Hospital, from February to April, 2015. Fasting blood sample was collected from 139 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
6
9
0
Order By: Relevance
“…In hypertensive pregnant women, the serum levels of TC, TG and LDL significantly increased and the serum level of HDL significantly decreased in the 3 rd trimester of pregnancy relative to those in the 2 nd trimester. The decreased levels of HDL in the 3rd trimester of hypertensive pregnant women in our study are in agreement with already published reports (Rabia et al, 2013;Ali et al, 2017;Alemu et al, 2018). From the results of our study, it can be found that serum levels of TC, TG, HDL, and LDL are more profound in the 3rd trimester of pregnancy in hypertensive pregnant women as compared to that of normotensive pregnant women (Table 7).…”
Section: Control Groupssupporting
confidence: 93%
See 1 more Smart Citation
“…In hypertensive pregnant women, the serum levels of TC, TG and LDL significantly increased and the serum level of HDL significantly decreased in the 3 rd trimester of pregnancy relative to those in the 2 nd trimester. The decreased levels of HDL in the 3rd trimester of hypertensive pregnant women in our study are in agreement with already published reports (Rabia et al, 2013;Ali et al, 2017;Alemu et al, 2018). From the results of our study, it can be found that serum levels of TC, TG, HDL, and LDL are more profound in the 3rd trimester of pregnancy in hypertensive pregnant women as compared to that of normotensive pregnant women (Table 7).…”
Section: Control Groupssupporting
confidence: 93%
“…But the serum level of HDL was significantly low in case groups relative to the control groups (P<0.05). This finding was similar with the finding of different previous published studies (Roohi et al, 2015;Pusukuru et al, 2016;Rabia et al, 2013;Ali et al, 2017;Alemu et al, 2018) in which all reported that pregnant women as compared to non-pregnant had significantly increased total cholesterol, triglycerides and LDL-cholesterol (p<0.05) along with significantly lower level of HDL cholesterol (P <0.05). On the contrary, the finding of this study was not in line with the finding of a case-control study done in India which reported that the changes in lipid profile were not significant as compared to controls (Chopra et al, 2017).…”
Section: Control Groupssupporting
confidence: 92%
“…It was known that plasma lipid levels, including those of triglyceride (TG) and total cholesterol (TC), were markedly higher in pregnant women than those in nonpregnant women, and were increased as gestation proceeds (Alemu et al, 2018;Wang et al, 2018). Compared with healthy control subjects, the levels of TG and TC were much higher in women with preeclampsia, gestational diabetes mellitus, and intrahepatic cholestasis of pregnancy (Pecks et al, 2016;Layton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Table (1) represents the TP and the activity and specific activity of Cp as (mean ± SE) for all studied groups . Table ( The different letters referred to significant differences, while similar letters referred to nonsignificant differences between the compared groups, P≤0.05 significant and P≥0.05 non-significant.…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy is a natural physiological condition characterized by metabolic and hormonal changes that help the fetus growth and survival. The metabolic, cardiovascular, renal, respiratory, and gastrointestinal systems of the body undergo physiological alterations [1]. Human gestation lasts about (40) weeks and is divided into three trimesters, start with fertilization and end with birth [2].…”
Section: Introductionmentioning
confidence: 99%